Moso bamboo invasion alters soil microbial nutrient limitation by modifying plant diversity and soil nutrient cycling in subtropical forest - Wang, Jiannan; Wen, Shihao; Liu, Weiqiang; Hao, Zitian; Wu, Xiuping; Peng, Sili; Ge, Zhiwei; Lin, Xiaoyue; Mao, Lingfeng (Frontiers in Plant Science, 2025)
IntroductionIn recent years, increasing management costs and declining market prices for Moso bamboo (Phyllostachys edulis) have led to the abandonment of many Moso bamboo forests, resulting in their gradual encroachment into neighboring broadleaf forests—a phenomenon that continues to intensify in subtropical regions of China. Moso bamboo invasion has significant impacts on ecosystem processes and functions; however, its effects on soil microbial nutrient limitations remain unclear.MethodsHere, we employed a space-for-time substitution by selecting plots representing four stages of Moso bamboo invasion and measuring plant community diversity, soil physicochemical properties, and extracellular enzyme activities related to carbon, nitrogen, and phosphorus cycling.ResultsResults showed that bamboo invasion reduced overstory (tree layer) diversity but increased diversity in the shrub and herb layers. Soil total organic carbon (TOC), total nitrogen (TN), available phosphorus (AP), and available potassium (AK) all decreased significantly with increasing invasion intensity. In contrast, soil pH and the activities of β-1, 4-glucosidase (BG), N-acetyl-β-glucosaminidase + leucine aminopeptidase (NAG+LAP), and acid phosphatase (ACP) increased along the invasion gradient. Throughout the invasion process, microbial C limitation intensified (longer vector length), whereas P limitation was partially alleviated (vector angle decreased). These shifts in microbial nutrient limitation were closely related to changes in soil nutrient content and plant diversity.DiscussionOur findings indicate that Moso bamboo invasion alters soil microbial nutrient acquisition strategies by reducing carbon inputs (enhancing C limitation) and relatively relaxing P limitation. These microbial nutrient limitation changes correspond with reduced tree litter and increased shrub/herb presence. The study provides new insights into invasion ecology and offers guidance for managing Moso bamboo spread in subtropical forests.